2008
DOI: 10.1063/1.2987733
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz-type relationship of the temperature dependent dielectric permittivity in ferroelectrics with diffuse phase transition

Abstract: The temperature dependence of the dielectric permittivity of perovskite Ba͑Zr x Ti 1−x ͒O 3 solid solutions, PbMg 1/3 Nb 2/3 O 3 relaxor, and BaTiO 3 ferroelectric ceramics was measured. It is found that a Lorentz-type law can be used to describe the dielectric permittivity of either the normal ferroelectrics with or without diffuse phase transitions ͑DPT͒ or the typical ferroelectric relaxors. The ferroelectric DPT can be well described by just one fitting process using the Lorentz-type law, while the relaxor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…The relaxor dispersion degree around T m1 can be estimated by the Lorentz-type relation, [ 21 ] 2 , where T A ( T A ≠ T m1 ) and ε A are the temperature of the dielectric permittivity peak and the extrapolated value of ε at T = T A , respectively. The parameter δ A refl ects the relaxor diffuseness of the dielectric peak.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…The relaxor dispersion degree around T m1 can be estimated by the Lorentz-type relation, [ 21 ] 2 , where T A ( T A ≠ T m1 ) and ε A are the temperature of the dielectric permittivity peak and the extrapolated value of ε at T = T A , respectively. The parameter δ A refl ects the relaxor diffuseness of the dielectric peak.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…It is found that ε r (T) can be fitted quite well by Eq. Table 1 Curve fitting results at 10 kHz for BCTZ ceramics suggested there should be one polarization process for the fitting parameters δ being close in two temperature ranges T > T m and T < T m , and two polarization processes for the larger difference of δ in ceramics, one dominating in the high and the other in the low temperature range [14]. But the largest diffuseness (δ ≈ 100 • C) of the permittivity peak in x = 0.01 sample, which is in contradiction with the experiment shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Besides, since e 0 m and T m used to determine the diffuseness parameter c using Eq. (7) are frequency dependent for relaxor materials, c is therefore not adequate to describe the frequency independent dielectric behavior at high temperatures (T > T m ) [33]. Hence the e 0 (T) data shown in Fig.…”
Section: Dielectric Studiesmentioning
confidence: 96%
“…5 was further analyzed to understand the origin for the observed frequency dependent diffused phase transition. It has been emphasized in the reported literature that a description of the high temperature slope of the dielectric peak in ferroelectrics with or without diffused phase transition (DPT), and classical relaxor materials can be well described above and below T m with the Lorenz type empirical relation [29,33,34]:…”
Section: Dielectric Studiesmentioning
confidence: 99%